Development Of Students' Logical Competence Through The Improvement Of Software And Information Support In The Context Of Digitalization (Eurasian Research Bulletin, 2025)
This article examines the problems of developing students' logical competence using logical problems from the vector chapter of geometry. Logical problems and the didactic requirements for them, as well as the features of solving logical problems using digital educational technologies, are analyzed. The importance of teaching students analytical and systematic thinking through logical problems in modern education is highlighted.